Pengaturan dan penerapan Tunjangan Hari Raya Berdasarkan Surat Edaran Menteri Ketenagakerjaan Nomor M/6/Hk.04/IV/2021: Studi RSIA Permata Hati Kota Mataram - Muhamad Sapoan; Lalu Hadi Adha (Fakultas Hukum Universitas Mataram, 2022)
This research aims to find out the implementation of religious holiday allowance to the labor based on the law, and the implementation of religious holiday allowance to the labors at Permata Hati Maternal and Child Hospital based on the Circular of the Minister of Manpower Number M/6/HK.04/IV/2021. The method of this research is empirical legal research using statute, conceptual, and sociological approaches. The data have been used in this research is primary and secondary data. The result of this research shows that healthy private company of Permata Hati Maternal and Child Hospital in Mataram City implementing religious holiday allowance based on the Government Regulation Number 36 of 2021 Concerning Wages which is regulated in Article 8 paragraph 1 and Article 9, Ministerial Regulation No. 6 of 2016 concerning the implementation of Religious Holiday Allowance, and the Circular of the Minister of Manpower Number M/6/HK.04/IV/202. Company provides allowances with the deadline systems, 7 days before Eid al-Fitr through bank account or direct face to face and the company provide benefit to labors in accordance with Regulation of the Minister of Manpower in force.